Effect of a Theory of Planned Behavior–Based Video on Attitude, Perceived Behavioral Control, and Consumption Intention among University Students - Komang Alan Ariadi; Yosef Wijoyo (Universitas Pahlawan Tuanku Tambusai, 2026)
Alcohol consumption among university students remains a public health concern. Guided by the Theory of Planned Behavior (TPB), this study evaluated a TPB-based educational video compared with presentation-based education in modifying attitude, subjective norm, perceived behavioral control (PBC), and alcohol consumption intention. A quasi-experimental pretest–posttest control group design was conducted with 120 students allocated to an educational video group (n = 60) or a presentation group (n = 60). Outcomes were assessed at baseline, two weeks, and four weeks post-intervention. Friedman, Wilcoxon, Mann–Whitney U, and Spearman correlation tests were applied, with baseline equivalence confirmed. Both groups showed significant within-group improvements (p < 0.05). Between-group analysis indicated greater reductions in favorable attitudes at both follow-ups and greater sustained improvement in PBC in the video group (p < 0.05), with small-to-moderate effect sizes (r = 0.23–0.29). No between-group differences were observed for subjective norm or intention, although intention declined in both groups. PBC showed the strongest association with intention. In conclusion, a brief TPB-based educational video more effectively strengthened internal behavioral determinants, particularly attitude and short-term PBC. However, comparable changes in subjective norm and intention suggest that reductions in alcohol-related intention may require complementary strategies addressing peer influence and social norms